Comments on Luke Nottage’s Paper - Kolsky Lewis, Meredith (Victoria University of Wellington Law Review, 2005)
The author comments on Luke Nottage’s paper found in this volume (Luke Nottage "Who’s Afraid of the Vienna Sales Convention (CISG)? A New Zealander’s View from Australia and Japan" (2005) 36 VUWLR 815). The author first identifies additional factors as to why the Convention on Contracts for the International Sale of Goods (’CISG’) may be opted out of in the United States: its lack of a duty of good faith, its narrow scope, and its uncertainty of outcome. However, the author argues that we should be more optimistic about the use of the CISG in the US. First, the US is an original signatory. Secondly, Americans may come to accept the CISG more as their exposure to it grows. Thirdly, a lack of reported US cases involving the CISG does not necessarily mean it is not being used – it purely indicates a lack of litigation. Fourthly, the CISG not being used may speak more about who the US are doing business with. Finally, the numbers show that the CISG is being used frequently. The author therefore concludes that we should be optimistic about the use of the CISG in the United States, and expects its use will increase over time.